The Effectiveness of Using Educaplay-Based Teaching Media for Teaching Vocabulary of The Tenth Grade StudentsiIn SMA 2 Bae - Ayuningrum, Devina (Applied Research on English Education (AREE), 2024)
In learning English, vocabulary is important because it helps students easier to convey what they want to say. The more vocabularies the students master, the easier  to learn English. In this case, there are still many students who lack of vocabulary mastery. This research aims to find out whether the use of Educaplay-Based Teaching is effective for teaching vocabulary to tenth grade students of SMA Negeri 2 Bae Kudus in academic year 2023/2024. Media is a tool in teaching and learning. Teaching by using media is needed in teaching learning processes to help students become active. Media have important roles in teaching-learning process. The use of media can help teacher and students to achieve the aims of teaching and learning.In this research, researcher used quantitative methods, and the design of this research was pre-experimental. The population in this research amounted to 360 students, with 36 students as samples in this study who came from classes X-E10. Researchers used oral tests in conducting this research.Based on the results of the study, the average score students before being taught using Educaplay was 57.91, and the average score of students after being taught using Educaplay was 76.94. The t value of this research is 14.31 with 35 degrees of freedom, and the t-table obtained with α = 0.05 was 1.689. So, it can be seen that 14,31 > 1,689. It means that the null hypothesis is rejected and the alternative hypothesis is accepted. It can be said that the use of Educaplay-Based Teaching is effective for teaching vocabulary to tenth grade students of SMA Negeri 2 Bae Kudus in academic year 2023/2024. Keywords: Speaking Skill, Educaplay, Teaching Vocabulary